KAJIAN DESKRIPTIF STRUKTURAL WACANA GRAFITI PADA TRUK - Junawaroh, Siti (HUMANIKA, 2015)
This paper is entitled â€œA Descriptive Study of Graffiti Discourse Structure on Trucksâ€. This research discusses about language unity form on the trucks.The purpose of this research is to describe writing language unity on the truck which consists of words, phrases, clauses and sentences of writing on the trucks. The method used in this research was qualititative descriptive and the techniques used was observationtechnique. Here, the writer usedrecorded and written techniqueduring this research. In analyzing data, the writer usessubtitution method.. According to the analysis on the data, the writing on the truk is decrypted according to language unity in the form of words, phrases, clauses, and sentences. The words found are in the form of nouns, verbs, and adjectives. The phrases found arein the form of nominal subordinative phrases, nominal coordinative phrases, verb subordinative phrases, and adjectival subordinative phrases. The clauses found includes S-P, P-S, and S-P-The sentences which are found are declarative sentencesand affirmative sentences.